The Existence of Nasi Grombyang Warso in Pemalang Regency (1978-1992) - Wardhana, Annas Eka; Abrar, Abrar; Humaidi, Humaidi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The aims of this study is to reconstruct the history of Nasi Grombyang Warso since he began his business until he succeed having his own food stall. This study used the historical method. Data collection techniques are documentation and interview. The findings from this study are several things that make Nasi Grombyang Warso become an icon in Pemalang Regency. As a traditional culinary dish that has a distinctive savory and spiced taste. Nasi Grombyang Warso is able to face the times. Warso is a Nasi Grombyang seller who is able to survive in Pemalang and has managed to maintain the recipe, despite changes in the form of presentation and use of ingredients. Maintaining traditional culinary delights such as Nasi Grombyang is something important and a concern for all of us in maintaining its sustainability. Assuming that throught this Nasi Grombyang culinary delights that have unique flavors in the Pemalang area and cannot be found in other areas. Apart from that, it is hoped that this article will become a reference in advancing tourism in Pemalang.